2017
DOI: 10.1097/igc.0000000000001025
|View full text |Cite
|
Sign up to set email alerts
|

Is Tumor Size Really Important for Prediction of Lymphatic Dissemination in Grade 1 Endometrial Carcinoma With Superficial Myometrial Invasion?

Abstract: Our results suggest that lymphadenectomy may be omitted in women with FIGO grade 1 EEC having superficial MMI regardless of PTD. Deferral of systematic LND in this subgroup of patients may lead to reductions in costs and surgical morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…The results of the pooled analysis revealed that tumor size >20 mm was significantly associated with LNM (OR = 4.11, 95% CI [3.63, 4.66], p < 0.001, I 2 = 0%, p = 0.73). A total of 20,735 patients in FIGO stage I–II endometrial cancer that were based on 6 studies ( 17 , 21 , 27 , 30 , 31 , 37 ) were enrolled in our meta-analysis. The pooled result showed that tumor size >20 mm was correlated with high LNM, and the pooled OR was 3.69 (95% CI [2.97, 4.60], p < 0.001), with heterogeneity (I 2 = 0%, p = 0.85).…”
Section: Resultsmentioning
confidence: 99%
“…The results of the pooled analysis revealed that tumor size >20 mm was significantly associated with LNM (OR = 4.11, 95% CI [3.63, 4.66], p < 0.001, I 2 = 0%, p = 0.73). A total of 20,735 patients in FIGO stage I–II endometrial cancer that were based on 6 studies ( 17 , 21 , 27 , 30 , 31 , 37 ) were enrolled in our meta-analysis. The pooled result showed that tumor size >20 mm was correlated with high LNM, and the pooled OR was 3.69 (95% CI [2.97, 4.60], p < 0.001), with heterogeneity (I 2 = 0%, p = 0.85).…”
Section: Resultsmentioning
confidence: 99%
“…The rate of LN involvement has been reported to be 1.46% (28/1,914) in this subgroup of patients in a Surveillance, Epidemiology, and End Results (SEER) data analysis [ 31 ]. In our previous study, LN involvement was not detected in any of the patients (n=120) with stage IA endometrioid type EC having FIGO grade 1 tumor and a PTD >2 cm [ 32 ]. Vargas et al [ 7 ] reported the same figure as 1.62% in another SEER data analysis including 3,816 patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current approach, systematic lymph node dissection is recommended for a primary tumor diameter >2 cm. [ 20 ] When tumor size increased, both tumor stage and grading were significantly increased. Moreover, tumor size was correlated with CA125 serum values, node metastasis and peritoneal cytology status.…”
Section: Discussionmentioning
confidence: 99%